track12 said:
y=x+(x^-1)
y= (x^2+1)/x
x^2+1= yx
x^2-xy+1= 0
y (plus or minus) the square root of ((-y)^2 - 4) divided by 2
y (plus or minus) (y-16)/2 <== How did this happen?
y (plus or minus) (y/2)-8 <== How did this happen?
x=(3y/2)-8
You have the following:
. . . . .\(\displaystyle y\, =\, x\, +\, \frac{1}{x}\)
You converted to the common denominator:
. . . . .\(\displaystyle y\, =\, \frac{x^2\, +\, 1}{x}\)
You then multiplied through by "x":
. . . . .\(\displaystyle xy\, =\, x^2\, +\, 1\)
Then you moved everything over together onto one side of the "equals" sign:
. . . . .\(\displaystyle 0\, =\, x^2\, -\, xy\, +\, 1\)
Now apply the Quadratic Formula to solve for x in terms of y:
. . . . .\(\displaystyle x\, =\, \frac{-(-y)\, \pm \, \sqrt{(-y)^2\, -\, 4(1)(1)}}{2(1)}\)
. . . . .\(\displaystyle x\, =\, \frac{y\, \pm \, \sqrt{y^2\, -\, 4}}{2}\)
But I don't understand what you did after this...? How did y[sup:j7wcc6s9]2[/sup:j7wcc6s9] - 4 become y - 16...?
(The "x=" is the inverse, though obviously it's not a function.)
Eliz.